Information System for Management of Savings and Loan Group Data at PNPM Peukan Baro Subdistrict, Pidie Regency - Yunita, Tuti (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The National Program for Community Empowerment (PNPM-MPd) has played a significant role in improving the welfare of rural communities, especially through its savings and loan groups aimed at empowering women. However, PNPM Peukan Baro Subdistrict still relies on outdated, manual methods using Microsoft Word and Excel for managing data, leading to inefficiency and delays. This study developed an information system using Microsoft Visual BASIC 6.0 and Microsoft Access to automate and improve data management. The system streamlines tasks such as member registration, loan tracking, savings entries, and payment management, ensuring faster data processing, fewer errors, and more accurate reports. The development process included feasibility analysis, user requirement gathering, system design, and implementation. The new system's design focuses on simplicity and user-friendliness, making it accessible to both administrators and group members with limited technical knowledge. After thorough testing and training, the system is expected to improve transparency, accelerate operations, and enhance decision-making within PNPM Peukan Baro. Ultimately, this shift from manual processes to a computerized system aims to support the overall success and efficiency of community empowerment efforts in the region